2020
DOI: 10.1021/acssensors.0c00664
|View full text |Cite
|
Sign up to set email alerts
|

Single-Entity Approach to Investigate Surface Charge Enhancement in Magnetoelectric Nanoparticles Induced by AC Magnetic Field Stimulation

Abstract: Magneto-electric nanoparticles (MENPs), composed of a piezoelectric shell and a ferromagnetic core, exhibited enhanced cell uptake and controlled drug release due to the enhanced localized electric field (surface charge/potential) and the generation of acoustics, respectively, upon applying alternating current (AC) magnetic (B)-field stimulation. This research, for the first time, implements an electrochemical single-entity approach to probe AC B-field induced strain mediated surface potential enhancement on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…It was performed in triplicate and shown as mean. 50,51 Drug Entrapment Efficiency Entrapment efficiency (EE) of rosuvastatin SNEDDS was examined as per the procedure established by Ke et al In brief, the content of free rosuvastatin was separated from SNEDDS by the ultrafiltration method (3500 Da) with centrifugation at 3000 g for 5 minutes followed by qualification using UV spectrophotometer at 242 nm. The EE was calculated as follows:…”
Section: Analysis Of Drug Contentmentioning
confidence: 99%
“…It was performed in triplicate and shown as mean. 50,51 Drug Entrapment Efficiency Entrapment efficiency (EE) of rosuvastatin SNEDDS was examined as per the procedure established by Ke et al In brief, the content of free rosuvastatin was separated from SNEDDS by the ultrafiltration method (3500 Da) with centrifugation at 3000 g for 5 minutes followed by qualification using UV spectrophotometer at 242 nm. The EE was calculated as follows:…”
Section: Analysis Of Drug Contentmentioning
confidence: 99%
“…The tetragonal crystal structure of the BaTiO 3 shell and the cubic structure of the CoFe 2 O 4 core has been shown using X-ray diffraction (XRD) [ 30 ]. Microscopy images of MENs show an irregular-sphere-like morphology [ 98 , 99 ]. MENs offer advantages in that they are able/show potential to (i) achieve targeting driven by an external magnetic force, (ii) provide on-demand externally controlled drug release and (iii) provide image-guided precision drug delivery [ 30 ].…”
Section: Drug Permeation Challenges In Cns Tb Treatmentmentioning
confidence: 99%
“…Furthermore, focused ion beam transmission electron microscope (FIB-TEM) analysis of microglial cells demonstrated a non-agglomerated distribution of MENs inside the cell and no loss of their elemental crystalline characteristics [ 105 ]. Pandey et al [ 98 ] demonstrated that MENs displayed enhanced cell uptake (via microglial brain cells) and controlled drug release. The authors further confirmed that the AC-magnetic field stimulated at 60 Oe confirmed the localized surface potential enhancement of MENs.…”
Section: Drug Permeation Challenges In Cns Tb Treatmentmentioning
confidence: 99%
“…Recent studies established engineered SPIONs using either a combination of hybrid concept or surface attachment of fluorescent probes in multistep synthesis processes. Kaushik et al extensively developed the various magneto-optical and magneto-electric nanosystems for magnetic field guided drug delivery and cancer therapy in biomedical applications. Chen et al designed silica coated magnetic nanoparticles combined with fluorescent quantum dots (QDs) as multimodal imaging probe . Feld et al fabricated hybrid quantum dots/quantum rods with tunable magnetic and fluorescent properties for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%